Dynamic evolution of the alpha (a) and beta (ß) keratins has accompanied integument diversification and the adaptation of birds into novel lifestyles - Greenwold, M.; Bao, W.; Jarvis, E.; Hu, H.; Li, C.; Gilbert, Thomas; Zhang, G.; Sawyer, R. (Biomed Central, 2014)
Background: Vertebrate skin appendages are constructed of keratins produced by multigene families. Alpha (a) keratins are found in all vertebrates, while beta (ß) keratins are found exclusively in reptiles and birds. We have studied the molecular evolution of these gene families in the genomes of 48 phylogenetically diverse birds and their expression in the scales and feathers of the chicken.Results: We found that the total number of a-keratins is lower in birds than mammals and non-avian reptiles, yet two a-keratin genes (KRT42 and KRT75) have expanded in birds. The ß-keratins, however, demonstrate a dynamic evolution associated with avian lifestyle. The avian specific feather ß-keratins comprise a large majority of the total number of ß-keratins, but independently derived lineages of aquatic and predatory birds have smaller proportions of feather ß-keratin genes and larger proportions of keratinocyte ß-keratin genes. Additionally, birds of prey have a larger proportion of claw ß-keratins. Analysis of a- and ß-keratin expression during development of chicken scales and feathers demonstrates that while a-keratins are expressed in these tissues, the number and magnitude of expressed ß-keratin genes far exceeds that of a-keratins.Conclusions: These results support the view that the number of a- and ß-keratin genes expressed, the proportion of the ß-keratin subfamily genes expressed and the diversification of the ß-keratin genes have been important for the evolution of the feather and the adaptation of birds into multiple ecological niches.